2021
DOI: 10.1002/jrsm.1498
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analytic structural equation modeling made easy: A tutorial and web application for one‐stage MASEM

Abstract: Meta-analytic Structural Equation Modeling (MASEM) refers to fitting structural equation models (such as path models or factor models) to meta-analytic data. Currently, fitting MASEMs may be challenging for researchers that are not accustomed to working with R software and packages. Therefore, we developed webMASEM; a web application for MASEM. This app implements the one-stage MASEM approach, and allows users to apply MASEM in a user-friendly way. The aim of this article is to provide a tutorial on one-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…Second, benevolent and hostile scales are correlated, so positive correlation between benevolent sexism and male-to-female violence may be due to its association with benevolent and hostile sexism. To estimate the unique effects that hostile and benevolent sexism exert on the attitudes toward violence or violent behaviour we used one-stage Meta-Analytic Structural Equation Modeling (MASEM) using Shiny app "webMASEM" (Jak et al, 2021). MASEM is an appropriate technique when one needs to test a SEM (e.g., a path model) on the averaged correlations between research variables across several studies (Jak et al, 2021).…”
Section: Meta-analysis Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, benevolent and hostile scales are correlated, so positive correlation between benevolent sexism and male-to-female violence may be due to its association with benevolent and hostile sexism. To estimate the unique effects that hostile and benevolent sexism exert on the attitudes toward violence or violent behaviour we used one-stage Meta-Analytic Structural Equation Modeling (MASEM) using Shiny app "webMASEM" (Jak et al, 2021). MASEM is an appropriate technique when one needs to test a SEM (e.g., a path model) on the averaged correlations between research variables across several studies (Jak et al, 2021).…”
Section: Meta-analysis Proceduresmentioning
confidence: 99%
“…To estimate the unique effects that hostile and benevolent sexism exert on the attitudes toward violence or violent behaviour we used one-stage Meta-Analytic Structural Equation Modeling (MASEM) using Shiny app "webMASEM" (Jak et al, 2021). MASEM is an appropriate technique when one needs to test a SEM (e.g., a path model) on the averaged correlations between research variables across several studies (Jak et al, 2021). The bivariate correlations between the three variables (benevolent sexism, hostile sexism, and attitudes toward violence/violent behaviour) were used in this analysis.…”
Section: Meta-analysis Proceduresmentioning
confidence: 99%
“…We used a one-stage Meta-Analytic Structural Equation Modeling (MASEM; Jak, 2015;Jak et al, 2021). This method is a random-effects technique and combines the methods of meta-analysis and SEM to fit a path model from a set of correlation matrices.…”
Section: Analysis and Data Preparationmentioning
confidence: 99%
“…Given our primary interest in testing a theoretical sequence, we planned to synthesize data from primary studies statistically within a meta-analytic structural equation modeling (MASEM) framework (Cheung, 2015; Jak et al, 2021). A statistical test of Wildman et al (2012) model in its entirety requires at least one observed correlation coefficient between each of the variable pairs in the averaged correlation matrix (Jak et al, 2021).…”
Section: Methodsmentioning
confidence: 99%